(untitled) (مجلة البحوث الأكاديمية, 2023)
Polymethyl methacrylate is the most widely used material for the construction of denture bases. Attempts have been made to improve the mechanical properties of this material. The purpose of this study was to evaluate some properties of the proprietary material known, commercially, as high impact resins, the microwave cured resin, and to compare them with the conventional heat- cured resins. The results showed that the high- impact denture base materials had higher impact strength, transverse strength, and deflection compared to the conventional and microwave cured resins. The tensile strength, modulus of elasticity were higher in the conventional and microwave cured resins but without statistically significant differences between the groups. Packing plasticity showed the highest values for the SR Ivoclar material (high impact resin), followed by the conventional heat-cured acrylic resins and the microwave cured acrylic resin. Within the high impact resins group, the SR Ivoclar material showed the best results in all properties studied. On the other, hand there was no significant difference between the properties of heat and microwave cured resins. All properties for the different studied materials complied with the ADA specification for the denture base polymers.